An In‐situ glucose‐stimulated insulin secretion assay under perfusion bioreactor conditions. (16th December 2016) - Sharp, Jamie; Vermette, Patrick
Abstract : Perfusion bioreactors, unlike traditional in vitro cell culture systems, offer stringent control of physiological parameters such as pH, flow, temperature, and dissolved oxygen concentration which have been shown to have an impact on cellular behaviour and viability. Due to the relative infancy and the growing interest in these in vitro culture systems, detection methods to monitor cell function under dynamic perfusion bioreactor conditions remains one of the main challenges. In this study, INS‐1 cells, a cell line which exhibit glucose‐stimulated insulin secretion, were embedded in fibrin and cultured under perfusion bioreactor conditions for 48 h and then exposed to either a high‐, or low‐glucose concentration for 24 h. These cultures were compared to non‐bioreacted controls. Bioreacted cultures exposed to a high‐glucose concentration showed the highest glucose‐stimulated insulin secretion when compared to those in a low‐glucose environment. The stimulation index, a marker for insulin secretion functionality, increased over time. A lower incidence of apoptotic cells was observed in the bioreacted cultures when compared to non‐bioreacted ones, as evaluated by a TUNEL assay. Immunofluorescence staining of Ki67 and insulin was performed and showed no differences in the incidence of proliferative cells between conditions (bioreacted and non‐bioreacted), where all cells stained positive for insulin. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:454–462, 2017